2023
DOI: 10.1007/s10384-023-00979-8
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy, durability, and safety of faricimab with extended dosing up to every 16 weeks in Japanese patients with diabetic macular edema: 1-year results from the Japan subgroup of the phase 3 YOSEMITE trial

Abstract: Purpose To evaluate efficacy, durability, and safety of faricimab in Japanese patients with diabetic macular edema (DME). Study design Subgroup analysis of 2 global, multicenter, randomized, double-masked, active-comparator-controlled, phase 3 trials (YOSEMITE, NCT03622580; RHINE, NCT03622593). Methods Patients with DME were randomized 1:1:1 to intravitreal faricimab 6.0 mg every 8 weeks (Q8W), faricimab 6.0 mg per personalized treatment interval (PTI), or aflibercept 2.0 mg Q8W through week 100. Primary endpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…These results are consistent with those of the YOSEMITE and RHINE studies, which reported that the efficacy of faricimab was not inferior to that of aflibercept 2 . In addition, a subgroup analysis of patients in the YOSEMITE and RHINE trials revealed similar results in Asian and non-Asian countries 8 and when limited to the patients in Japan 9 . Kusuhara et al reported that the overall mean CMT after switching from IVA to IVF decreased significantly from the baseline value 1 month after administration 10 .…”
Section: Discussionmentioning
confidence: 71%
“…These results are consistent with those of the YOSEMITE and RHINE studies, which reported that the efficacy of faricimab was not inferior to that of aflibercept 2 . In addition, a subgroup analysis of patients in the YOSEMITE and RHINE trials revealed similar results in Asian and non-Asian countries 8 and when limited to the patients in Japan 9 . Kusuhara et al reported that the overall mean CMT after switching from IVA to IVF decreased significantly from the baseline value 1 month after administration 10 .…”
Section: Discussionmentioning
confidence: 71%
“…For recurrent edema, the prognosis for vision is poor if injections are not administered promptly; thus, administering a sufficient number of injections is recommended 21 . Although frequent injections increase the economic burden on patients 22 , new anti‐VEGF agents such as brolucizumab and faricimab have been developed for diabetic macular edema, and regimens with longer dosing intervals have been proposed 23 , 24 , 25 . Advances in drug therapy are expected to reduce the visual impairment caused by diabetic macular edema in the future.…”
Section: Discussionmentioning
confidence: 99%